2010
DOI: 10.1021/jf102193k
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Activity ofAsarum heterotropoidesRoot Constituents against Insecticide-Susceptible and -ResistantCulex pipiens pallensandAedes aegyptiandOchlerotatus togoi

Abstract: We investigated the toxicity of (-)-asarinin, α-asarone, methyleugenol, pellitorine, and pentadecane identified in Asarum heterotropoides root to third instar larvae from insecticide-susceptible Culex pipiens pallens (KS-CP strain), Aedes aegypti, and Ochlerotatus togoi as well as field-collected C. p. pallens (DJ-CP colony), identified by polymerase chain reaction. Results were compared with those of two conventional mosquito larvicides: fenthion and temephos. Pellitorine (LC50, 2.08, 2.33, and 2.38 ppm) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 23 publications
2
75
0
Order By: Relevance
“…Anal papillae region and cuticle layer of treated larvae was damaged when compared with the control larvae (Fig. 7) Structural deformities of anal papillae may be intrinsically associated with the death of the treated mosquito larvae (Perumalsamy et al 2010).…”
Section: Light Micrographs Of Control and Treated Fourth Instar Larvaementioning
confidence: 99%
“…Anal papillae region and cuticle layer of treated larvae was damaged when compared with the control larvae (Fig. 7) Structural deformities of anal papillae may be intrinsically associated with the death of the treated mosquito larvae (Perumalsamy et al 2010).…”
Section: Light Micrographs Of Control and Treated Fourth Instar Larvaementioning
confidence: 99%
“…Thus, it is suggested that α-asarone is a major contributor to the larvicidal activity of the essential oil of Y. japonica. Moreover, compared with chlorpyrifos, α-asarone was 12 times less toxic to A. albopictus larvae ( [27,28]. Menthol also possessed larvicidal activity against the fourth instar larvae of A. aegypti with a 24-h LC 50 value of 365.8 ppm [29,30].…”
Section: Larvicidal Activitymentioning
confidence: 95%
“…Cypermethrin (Mugni et al 2011) is commonly used for the treatment of bed nets and as a residual spray to help control malaria transmission. Unfortunately, the widespread use and incorrect application of cypermethrin and other synthetic pyrethroids have accelerated the emergence of resistance in both targeted Anopheles species and off-target species such as Culex pipiens pallens (Perumalsamy et al 2010). The elucidation of the resistance mechanism becomes important to guide the use of cypermethrin and the development of its substitutes.…”
Section: Introductionmentioning
confidence: 99%